Modified heterocyclic aramid fiber as well as preparation method and application thereof

By introducing flexible monomers into the main chain of aramid molecule and using one-pot synthesis technology, the problems of core structure defects and poor solubility of aramid fibers during spinning are solved, and the solubleness and toughness of organic solvents are improved, and it is suitable for material applications in extreme environments.

CN120399217APending Publication Date: 2025-08-01EAST CHINA NORMAL UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510527845.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

During the spinning process, existing aramid fibers have problems such as core structure defects, poor solubility, high processing risk and high cost, and are difficult to dissolve in solvents other than concentrated sulfuric acid, which affects its application and safety.

Method used

By introducing flexible monomers, such as 4,4'-diaminodiphenylsulfone, etc. into the main chain of the aramid molecule, the one-pot synthesis technology is used to dissolve the modified heterocyclic aramid in an organic solvent to form the modified heterocyclic aramid, optimize the solvent system, avoid spinning of concentrated sulfuric acid, and improve the solubility and toughness of the fiber.

Benefits of technology

It realizes the solubleness of aramid fiber in organic solvents, reduces the risk and cost of the spinning process, improves the toughness and impact resistance of the fibers, broadens its application range, and is suitable for material needs in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399217A_ABST
    Figure CN120399217A_ABST
Patent Text Reader

Abstract

The invention discloses modified heterocyclic aramid fiber as well as a preparation method and application thereof. The modified heterocyclic aramid fiber has a structure as shown in a formula I, according to the preparation method, p-phenylenediamine (PPD), 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA), a bifunctional fourth monomer, terephthaloyl chloride (TPC) and the like are taken as raw materials, a proper organic solvent and a cosolvent are selected, the modified heterocyclic aramid fiber is prepared through low-temperature solution condensation polymerization, and the product is high in molecular weight, improved in solubility and easy to process and form. The raw materials are cheap and easy to obtain, the preparation method is simple, the reaction conversion rate is high, the process stability is high, and the method can be used for large-scale continuous production. The composite material has the advantages of high cost performance, flame retardance, self-extinguishing, heat insulation, insulation, wear resistance and the like. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of synthesis and application of high-performance materials, and particularly relates to a modified heterocyclic aramid which is easy to form, has high compatibility, high flame retardancy and self-extinguishing property, and a preparation method and application thereof. Background Art

[0002] Aramid has excellent properties. The molecular chain of para-aramid PPTA belongs to a straight-chain conformation, similar to a rod-shaped rigid regular structure, with less entanglement between molecules. The main chain of aramid is composed of aromatic rings and amide bonds. The aromatic ring structure has high rigidity, and the polymer chain forms a rod-shaped structure in an extended state. At the same time, the linear molecular chain structure of aramid makes the space utilization rate of aramid fibers high, so more polymers can be accommodated per unit volume, thus improving the strength. In addition, the conformation of the macromolecular chain is approximately linear, with a small cross-sectional area. The angular deformation and internal bond rotation of the polymer chain are subject to great resistance, and the relative molecular mass is large. Therefore, this material has excellent properties such as ultra-high strength, high modulus, high temperature resistance, acid and alkali resistance, and light weight. Para-aramid PPTA is insoluble in most organic and inorganic solvents, and its melting point is higher than the degradation temperature (about 500 °C), so melt spinning is impossible.

[0003] There are still problems in the processing of existing aramids. When spinning para-aramid, it needs to be dissolved in strong acid. During the spinning process of concentrated sulfuric acid, the equipment is severely corroded. In order to ensure long-term safe use, the material of the spinning equipment is expensive Hastelloy steel. At the same time, pressurized spinning in concentrated sulfuric acid is also a great challenge to the safety and health of personnel, and spinning workers also need to take strict protection measures. The post-treatment of a large amount of spinning solution containing sulfuric acid is equally dangerous and highly corrosive. The processing cost is high and the risk is great.

[0004] There are some problems in the structural properties of existing aramids. During the spinning process of para-aramid PPTA, the molecular chain will be further arranged along the fiber axis under the action of tensile force, making para-aramid have a high degree of orientation. However, there are only intermolecular hydrogen bonds and van der Waals forces formed by amide bonds between macromolecular chains. This interaction is weaker than covalent bonds, so that the macromolecular chains are easily cracked along the fiber longitudinal direction to form microfibrils. This microfibril structure and weak intermolecular force result in a low compressive strength of aramid PPTA. During axial compression, it will cause the fibers to kink and undergo compression failure. Aramid PPTA has an obvious skin-core structure. The orientation degree of the skin layer is higher than that of the core layer, but the crystallinity is lower.

[0005] When aramid PPTA is used as a reinforcing material in composites, the skin-core structure of aramid PPTA has a greater impact. The bonding force between the skin layer and the core layer is weak. In its composites, when stress is transferred from the resin matrix to the fiber, the fiber is prone to skin-core layer damage. Therefore, due to the harsh spinning conditions of para-aramid, the lateral cohesive properties of the fiber are weak, resulting in low compressive strength between the aramid and the matrix, and the interfacial interaction needs to be improved.

[0006] Para-aramid fiber is a high-strength, high-modulus, and high-temperature-resistant organic fiber. Its tensile strength can reach 5.0 GPa, its tensile modulus can reach 150 GPa, and its decomposition temperature reaches 560 °C. It is the main material for preparing products such as rocket engine casings, bulletproof vests, tank composite armor, and high-strength cables.

[0007] Chinese Patent Application CN118854479A discloses a method for preparing white para-aramid fiber. In the method for preparing high-thermal-conductivity para-aramid fiber, the weight ratio of hexagonal boron nitride to concentrated H2SO4 is 1:(15 - 300), and the mass concentration of concentrated H2SO4 is not less than 99.8%; the method still requires concentrated H2SO4 for spinning, and the subsequent treatments are steps such as alkali washing and water washing, with complex operations and high risks. US-20240368808-A1 reports a para-aramid short fiber, which improves the yarn's anti-cutting property by applying a draw ratio of 4% or higher; however, the prepared para-aramid polymer needs to be dissolved in H2SO4 to prepare a spinning coating; there are also problems such as complex operations and harsh dissolution conditions.

[0008] Chinese Patent 201010108545.6 discloses a high-performance heterocyclic aramid machine preparation and application, using wet spinning. To be suitable for wet spinning, it is necessary to further increase the dissolution concentration of aramid III in the solvent, thereby improving the spinning efficiency and reducing its cost.

[0009] Aramid III is a modified para-aramid. Problems existing in the existing modified aramid: In aramid III, when the content of heterocyclic compounds is low, its dissolution performance is similar to that of para-aramid, so the spinning conditions required are similar to those of para-aramid, that is, concentrated sulfuric acid spinning is required. If the content of heterocyclic compounds is high, it will cause the performance to be slightly lower than that of para-aramid PPTA. Therefore, it is necessary to adjust a suitable formula and composition to achieve all the advantages of para-aramid and aramid III in the prepared aramid product from the perspective of mechanical properties, and have a new modified aramid copolymer. It is expected to prepare an aramid modified polymer that retains the original high strength and high modulus and can be dissolved in a specific organic solvent system, which is beneficial to spinning and easy to recycle the spinning solution.

[0010] The existing preparation methods of aramid fibers need to go through process steps such as polymer synthesis, preparation of polymer spinning solution, spinning and forming, winding and cutting, etc. The process flow is long, special equipment is required, and the cost is expensive. Aramid ultra-short fibers have attracted people's attention because of their advantages such as good heat resistance, non-melting, non-flammability, easy forming and processing, and low cost.

[0011] The problem of the existing technology is that poly(p-phenyleneterephthalamide) (PPTA) is usually prepared by low-temperature solution polycondensation. The prepared polymer is a yellow solid powder. The conformation of the macromolecular chain is approximately linear, the cross-sectional area is small, the angular deformation of the polymer chain and the resistance to bond internal rotation are large, the relative molecular mass is large, and it is difficult to dissolve in reagents other than concentrated sulfuric acid. Summary of the Invention

[0012] Based on this, the purpose of the present invention is to provide a modified heterocyclic aramid with high flame retardancy, self-extinguishing, easy to form and high compatibility, and its preparation method and application. Aiming at the skin-core structure defect of the fiber in the spinning process due to the strong hydrogen bond of the molecular structure of the existing para-aramid PPTA; and further improving the performance of the ternary aramid PPAI, also known as aramid III, and designing the molecular structure to further improve the processing performance and the regularity of the molecular structure of aramid.

[0013] In order to adapt to and further improve the spinning process of aramid, it is necessary to introduce a small amount of flexible monomers in the synthesis of modified heterocyclic aramid, so as to avoid the cracking problem of para-aramid and aramid III. Therefore, it is necessary to develop a special organic solvent that can dissolve, maintain a certain intermolecular hydrogen bond (which is beneficial to performance improvement), does not damage the rigidity of the para-aramid liquid crystal molecules, and can maintain a certain non-close-packed crystallinity, so as to improve the skin-core structure problem.

[0014] The specific technical solution to achieve the purpose of the present invention is:

[0015] A modified heterocyclic aramid, whose structural formula is as follows:

[0016]

[0017] In the formula,

[0018] m is 20 - 400; n is 20 - 400; r is 4 - 210;

[0019] Ar, the diamino fourth monomer, is the residue other than the amino group in the following compounds: 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 3,3'-diaminodiphenyl sulfone, 1,5-naphthalenediamine, 2,6-naphthalenediamine, 1,6-naphthalenediamine, 1,7-naphthalenediamine, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, 4-(4-amino-3,5-dimethylbenzyl)-2,6-dimethylaniline, or 3,3',5,5'-tetramethylbenzidine.

[0020] Specifically, Ar is as follows:

[0021]

[0022] A preparation method of the above-mentioned modified heterocyclic aramid, which is synthesized by a one-pot method, specifically includes:

[0023] Step 1: Synthesis of the crude modified heterocyclic aramid

[0024] In a reactor equipped with a nitrogen device and a thermometer, pure nitrogen is introduced, and then the dehydrated co-solvent and solvent are added and mixed and dissolved; p-phenylenediamine (PPD), 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA), and the fourth monomer are added, and the temperature is lowered to -20 to 0 °C; stirring is continued, and terephthaloyl chloride (TPC) is added in batches; an acid-binding agent is used to neutralize the by-product HCl generated by the polymerization reaction; the reaction time is extended to obtain a liquid crystal gel-like product, which is the crude product.

[0025] Step 2: Refinement of the modified heterocyclic aramid

[0026] The crude product obtained in Step 1 is precipitated, crushed, and thoroughly washed, and then dried to a constant weight in a vacuum drying oven to obtain a light yellow modified aramid pulp, that is, the ultra-short fiber polymer, which is the modified quaternary heterocyclic aramid; the specific synthesis route is shown in Formula (1):

[0027]

[0028] In Step 1, the solvent is one or more of N-methylpyrrolidone (NMP), N,N'-dimethylacetamide, N,N'-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO); preferably, it is N-methylpyrrolidone (NMP) and N,N'-dimethylacetamide;

[0029] The co-solvent is lithium chloride or calcium chloride;

[0030] The content of the co-solvent is 0.5-5 wt% of the total solution; preferably, it is 3-5 wt%.

[0031] In Step 1, the reaction temperature is -20 to 5 °C; preferably, it is 0 to 5 °C.

[0032] In Step 1, the reaction time is 90 to 240 minutes; preferably, it is 100 to 120 minutes.

[0033] In Step 1, the acid-binding agent is α-methylpyridine or pyridine; preferably, it is α-methylpyridine.

[0034] In the present invention, the terephthaloyl chloride can be added in two portions, aiming to increase the molecular weight of the aramid and control the reaction rate.

[0035] In the present invention, the mass ratio of terephthaloyl chloride TPC: p-phenylenediamine PPD: 2-(4-aminophenyl)-5-aminobenzimidazole APBIA: the fourth monomer: solvent: co-solvent: acid-binding agent is 1: 0.20 - 0.30: 0.13 - 0.46: 0.04 - 0.41: 9.47 - 37.90: 0.047 - 0.76: 0.17 - 0.84;

[0036] Use of the above-mentioned modified heterocyclic aramid in the preparation of aramid-polyurethane foam composites.

[0037] The modified heterocyclic aramid prepared by the method of the present invention can not only be directly post-treated to obtain short fibers, but also be used for spinning long fibers and medium-length fibers. It can also prepare copolymer aramid films with excellent properties, flame-retardant aramid papers, and aramid honeycombs with sound insulation, heat insulation and impact resistance, as well as aramid plates with flame-retardant effects, flame-retardant modification of ordinary foam plastics, etc.

[0038] By introducing a fourth monomer with different structures into the molecular main chain of binary aramid PPTA and ternary aramid PPAI, the present invention improves the solubility and fatigue resistance of the aramid while basically maintaining the original excellent properties. The present invention not only prepares modified heterocyclic aramid pulp short fibers with excellent properties through post-treatment of the polycondensation stock solution, but also can prepare modified heterocyclic aramid aerogels with excellent properties, expanding the application fields of aramid materials.

[0039] The present invention has different effects when introducing a fourth monomer with different structures into the ternary aramid PPAI molecule:

[0040] Introducing 4,4'-diaminodiphenyl sulfone improves toughness and the compatibility with organic solvents dimethyl sulfoxide, NMP and DMAC, which is beneficial to processing into long fibers in organic solvent / co-solvent.

[0041] The naphthalenediamine monomer introduces a rigid parallel-axis structural unit, which causes multiple turns in the molecular chain axis, reduces the coaxiality, partially destroys the regularity of the molecular chain, weakens the intermolecular hydrogen bonds, and improves the solubility of the system when the amount of naphthalene ring is small.

[0042] Compared with the prior art, the present invention has the following characteristics:

[0043] By adding a fourth monomer, the macromolecular chain structure of the ternary aramid PPAI is improved; different structures of the fourth monomer result in different material properties: the fourth monomer with a sulfone group can increase the toughness of the modified heterocyclic aramid and improve the fatigue resistance of the fiber; the modified heterocyclic aramid fiber of the present invention has good compatibility, improved molecular toughness and improved impact resistance; at the same time, all monomers have an aromatic ring structure, and the tensile resistance is still very high. This improvement in toughness is beneficial to maintaining the toughness and impact resistance of aramid under extremely cold conditions such as in the Antarctic and Arctic (-70 °C). And for airplanes on the ground near the equator at 56.7 °C to the polar regions (-70 °C), missiles, space shuttles (the temperature in the sky ranges from -45 °C to -80 °C; the average temperature in space is about -270 °C, but the temperature difference is large in different environments. Under direct sunlight, the temperature on the surface of the space station can be as high as over 150 °C, while on the shaded side, the temperature may be as low as below -100 °C.), submarines (the temperature at a depth of 1000 meters under the sea is about 4 °C and the pressure is 100 atmospheres; the pressure at a depth of 10000 meters under the sea is 1000 atmospheres, 101 MPa), high-speed rails, etc., where the temperature difference is large in a short time (the lowest temperature on the moon is -184 °C and the highest is 127 °C), the pressure changes greatly, or there is rapid cooling and heating in a short time. In such an environment, the material properties need to be stable, the aramid needs to maintain its strength, and at the same time, the toughness of the material is required to be increased. In such extreme cases, the toughness of para-aramid needs to be improved. The modified heterocyclic aramid of the present invention can just solve these problems.

[0044] By adding functional group monomers with anti-aging properties, the aging resistance of aramid fibers can be improved; by adding monomers resistant to ultraviolet light irradiation, the light resistance of the fibers can be improved, expanding the application fields of aramid; polycyclic aromatic hydrocarbons can further improve the heat resistance; the fourth monomer with functional groups can increase the dyeability of aramid fibers.

[0045] Optimizing the solvent system: Using a solvent system composed of an organic solvent - co-solvent chloride can be directly used as a spinning solution to prepare short fibers; there is no need for spinning with concentrated sulfuric acid, reducing instrument loss, reducing operation steps, saving time and reducing costs.

[0046] On the one hand, due to the addition of the fourth monomer in the present invention, and on the other hand, by optimizing conditions such as synthesis temperature, reaction time, and solvent system, an aramid liquid crystal effect is generated in the polymerization system, which helps to form modified heterocyclic aramid short fibers.

[0047] The modified heterocyclic aramid short fiber pulp prepared by the present invention can be further used to prepare aramid aerogels, aramid papers, aramid boards, etc.

[0048] The beneficial effects of the present invention are as follows:

[0049] In the process of preparing modified heterocyclic aramid of the present invention, one-pot synthesis is adopted, and the synthesis route and process operation are simple; moreover, the process is stable and has good repeatability, and it can be prepared under laboratory conditions. Therefore, in a factory, under the conditions of better stirring efficiency and instrument airtightness, it is easier to achieve industrial scale-up.

[0050] In the reaction of the present invention, the reaction time is short and the conversion rate is high. It is prepared by a low-temperature solution polycondensation process, without the need to raise the temperature, saving energy and reducing costs.

[0051] The modified heterocyclic aramid of the present invention has good compatibility and is easy to process and form, which can provide a new way for the synthesis, spinning and application of aramid polymers.

[0052] The raw materials used are widely sourced, inexpensive and easily available.

[0053] The modified heterocyclic aramid of the present invention has good compatibility, is easy to process, has a low price, and can be dissolved in a suitable organic solvent - cosolvent. Therefore, the processing conditions are mild and without danger; spinning under these conditions is safer than concentrated sulfuric acid, reducing equipment costs.

[0054] The advantage is that the spinnability of the modified heterocyclic aramid has improved; in order to achieve spinnability for the ternary aramid PPAI, a large amount of 2-(4-aminophenyl)-5-aminobenzimidazole is required, and this substance is expensive. Using a fourth monomer such as diaminodiphenyl sulfone reduces the cost of the aramid.

[0055] During the preparation of the modified heterocyclic aramid, when a fourth monomer is added, the dissolution performance of the modified heterocyclic aramid is improved.

[0056] When a fourth monomer such as diaminodiphenyl sulfone is added, the modified heterocyclic aramid is light yellow in color, which is beneficial for subsequent dyeing.

[0057] This invention opens up new uses for aramid, such as preparing new fire-resistant and high-temperature-resistant fireproof materials with wide applications; or compounding with polyurethane materials that are not heat-resistant to broaden their application scope;

[0058] The product modified heterocyclic aramid of the present invention has a microcrystalline morphology. Compared with the completely ordered DTPA, the heterocyclic monomer and the fourth monomer of the modified heterocyclic aramid can better enhance its dissolution performance, and at the same time, the local order also enables it to maintain excellent fire-resistant and high-temperature-resistant properties. There are a large number of hydrogen bonds on the surface of the locally ordered modified heterocyclic aramid. When compounded with other materials, a large range of hydrogen bond interconnections are formed, tightly connecting with other materials, endowing it with fire resistance and biological protection under extreme temperature conditions. Description of the Drawings

[0059] Figure 1 It is the infrared spectrum of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0060] Figure 2The wide-angle X-ray diffraction patterns (XRD) of the dried samples of the products obtained in Comparative Example 1, Comparative Example 2, Example 1, Example 8 and Example 3 of the present invention are shown;

[0061] Figure 3 The thermogravimetric graphs of the products obtained in Example 1, Example 8, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention at a temperature increase of 10°C / min are shown;

[0062] Figure 4 and Figure 5 This is a scanning electron microscope (SEM) photograph of a dry short fiber sample of the product obtained in Example 1 of the present invention;

[0063] Figure 6 This is an optical microscope image of Application Example 1 of the present invention. DETAILED DESCRIPTION

[0064] The present invention will be further described in detail with reference to the following specific embodiments and accompanying drawings.

[0065] Except for the contents specifically mentioned below, the processes, conditions, experimental methods, etc. for implementing the present invention are common knowledge and common common sense in the field and are not particularly limited by the present invention.

[0066] Example 1

[0067] One-pot preparation of modified heterocyclic aramid copolymer pulp staple fibers

[0068] The specific synthesis steps are as follows:

[0069] The first step is the synthesis of modified heterocyclic aramid crude product

[0070] In a reactor connected to a nitrogen device and a thermometer, pure nitrogen is ventilated for 20 minutes in advance, and then 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of N-methylpyrrolidone NMP are added, mixed and dissolved at room temperature, and 21.6 parts by mass of p-phenylenediamine PPD, 41 parts by mass of 2-(4-aminophenyl)-5-aminobenzimidazole APBIA, and 4.32 parts by mass of the fourth monomer 4,4'-diaminodiphenyl sulfone DDS are added in batches. During this process, in order to prevent oxidation and reduce the solution temperature, the system needs to be placed in a cooling circulation tank and cooled to -5°C, and stirring is continued;

[0071] 105.6 parts by mass of terephthaloyl chloride (TPC) were added in batches, and 75 parts by mass of 2-methylpyridine was used to neutralize the by-product HCl generated by the polymerization reaction. The reaction was continued for 120 to 150 minutes to obtain a gel-like product.

[0072] The second step is to modify the aramid products

[0073] After crushing and thoroughly washing it, it was dried in a vacuum drying oven at 150 °C for 8 hours until constant weight to obtain light yellow powdery modified heterocyclic aramid pulp short fibers; named PPAIS 45 , and the reaction yield was 94%; the average fiber length was greater than 5.1 mm; η inh was 5.65 dL / g (the inner diameter of the Ubbelohde viscometer was 1.0 - 1.2 mm).

[0074] The washing process included adding water to the obtained solution, and flocculates appeared; filtration was carried out, and it was stirred and washed three times with ethanol and water respectively to remove impurities;

[0075] PPAIS 45 The naming method means the molar ratio of PPD: APBIA: the fourth monomer DDS = 50:45:5.

[0076] In this example, the solvent NMP can be replaced by DMAC, DMF or DMSO, etc., and the technical effects described in this example can also be achieved.

[0077] In this example, the co - solvent calcium chloride can be replaced by lithium chloride or magnesium chloride, etc., and the good technical effects described in this example can also be achieved.

[0078] In this example, the diamine (amino) fourth monomer 4,4’ - diaminodiphenyl sulfone can be replaced by ductile 3,3’ - diaminodiphenyl sulfone; rigid 3,3’ - diaminodiphenylmethane, 4,4’ - diaminodiphenylmethane, flexible 4,4’ - diaminodiphenyl sulfide, 3,3’ - diaminodiphenyl sulfide; dyeing performance 4 - (4 - amino - 3,5 - dimethylbenzyl) - 2,6 - dimethylaniline, rigid 3,3’,5,5’ - tetramethylbenzidine, etc., and the good technical effects described in this example can also be achieved. 4,4’ - diaminodiphenyl sulfone can be replaced by rigid 1,5 - naphthalenediamine, 2,6 - naphthalenediamine, 1,6 - naphthalenediamine, 1,7 - naphthalenediamine, etc., and the good technical effects described in this example can also be achieved.

[0079] Appendix Figure 1 includes the modified heterocyclic aramid PPAIS of Example 1 45 The curve of the quaternary copolymer, the absorption peak is located at 1130 cm-1, corresponding to the stretching vibration of O = S = O in diaminodiphenyl sulfone, which also indicates the successful introduction of DDS into the aramid. Similarly, the peak at 1592 cm -1 corresponds to the vibration of the imidazole ring C - N in APBIA. The infrared spectrum of this example proves the successful progress of its low - temperature solution polycondensation reaction.

[0080] XRD is shown in Appendix Figure 2 Curve PPAIS 45; In the figure, there is a composite peak, indicating the existence of local structural order in the synthesized modified heterocyclic aromatic polyamide quaternary copolymer.

[0081] The thermogravimetric test results of this example are shown in the appendix Figure 3 , and the synthesized product was characterized and analyzed to prove that the modified heterocyclic aromatic polyamide PPAIS 45 has good thermal stability.

[0082] Figure 4 and Figure 5 are the scanning electron microscope SEM photos of the dry short fiber sample of the modified heterocyclic aromatic polyamide PPAIS 45 in this example; the fiber length is 5 mm and the diameter is 5 μm; the microscopic morphology of PPAIS 45 is local order and partial amorphous regions, with a microfibril structure.

[0083] Synthesize a modified heterocyclic aromatic polyamide quaternary copolymer, poly(aramide-imidazole-sulfone) PPAIS 45 The cross-section of the spinning sample has no obvious skin-fiber structure and shows obvious morphology characteristics of toughening and strengthening.

[0084] The product PPAIS in this example 45 has good solubility (see Table 2). In NMP solvent with 5wt% CaCl2 content and DMAC with 5wt% CaCl2 content, a yellow transparent solution can be obtained after stirring for a period of time. The modified heterocyclic aromatic polyamide quaternary copolymer is slightly swollen in DMAC and NMP; it is insoluble in THF, acetone, and toluene, retaining the insoluble characteristics of para-aramid, so the modified heterocyclic aromatic polyamide is resistant to organic solvents.

[0085] The modified heterocyclic aromatic polyamide PPAIS 45 in this example is a viscous liquid during the polymerization process, and the crude product is a liquid crystal gel. The SEM results show that this aramid has good local order and there are still a small amount of amorphous regions, so it can be dissolved in NMP(CaCl2) solution, which is beneficial to subsequent spinning and forming in NMP with 5wt% CaCl2 content. Synthesize a modified heterocyclic aromatic polyamide quaternary copolymer, poly(aramide-imidazole-sulfone) PPAIS 45 has no obvious skin-fiber structure and shows obvious morphology characteristics of toughening and strengthening.

[0086] In this example, the molecular structure design of sulfone groups in a small amount of flexible and rotatable diaminodiphenyl sulfone, non-rotatable benzene ring conjugation of regular and strong hydrogen bonds, and large-scale rigid fused-ring aminophenyl-aminobenzimidazole, on the one hand, realizes the feasibility of non-sulfuric acid spinning solution from the perspective of liquid crystal forming, and at the same time ensures the rigidity of the modified heterocyclic aromatic polyamide PPAIS 45 from the perspective of material mechanics, while providing better toughness. Therefore, it is easy to form pulp ultra-short filaments during post-treatment.

[0087] While improving the solubility, this modified heterocyclic aramid does not change its molecular weight. At the same time, its thermal stability and molecular order are improved to a certain extent, and its thermal stability above 500 °C is also enhanced, enabling it to have more applications in high-temperature fields.

[0088] Example 2

[0089] Preparation of Modified Heterocyclic Aramid Copolymer

[0090] The specific synthesis steps are as follows:

[0091] The First Step: Synthesis of Crude Modified Heterocyclic Aramid

[0092] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, and mix and dissolve at room temperature. Add 21.6 parts by mass of PPD, 41 parts by mass of APBIA, and 4.32 parts by mass of 1,5-naphthalenediamine in batches. During this process, to prevent oxidation and lower the solution temperature, place the system in a cooling circulation bath and cool it to -5 °C. Continue stirring and add 89.3 parts by mass of TPC in batches. Use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction, and react for 120 - 150 minutes to obtain a gel-like product;

[0093] The Second Step: Fine Modified Heterocyclic Aramid

[0094] After crushing and thoroughly washing it, dry it in a vacuum drying oven at 150 °C for 8 hours until constant weight to obtain light yellow pulp ultra-short fiber modified heterocyclic aramid, named PPAIN 45-1 . The monomer conversion rate is 93.56%. The average fiber length is greater than 5.0 mm; η inh is 5.30 dL / g.

[0095] Example 3

[0096] Preparation of Modified Heterocyclic Aramid Copolymer

[0097] The specific synthesis steps are as follows:

[0098] The First Step: Synthesis of Crude Modified Heterocyclic Aramid

[0099] In a four-necked flask equipped with a nitrogen device and a thermometer, purify the nitrogen and aerate for 10 minutes in advance, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, and mix and dissolve at room temperature. Add 21.6 parts by mass of PPD, 31.9 parts by mass of APBIA, and 1.30 parts by mass of DDS in batches. During this process, to prevent oxidation and lower the solution temperature, place the system in a cooling circulation bath and cool it to -5°C. Continue stirring and add 105.6 parts by mass of TPC in batches. Use 75 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction. React for 240 minutes to obtain a gel-like product.

[0100] Step 2 Modified heterocyclic aramid product

[0101] After pulverizing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain a light yellow pulp ultra-short fiber modified heterocyclic aramid copolymer, named PPAIS 35 . The monomer conversion rate is 88.51%. The average fiber length is greater than 5.2 mm; η inh is 4.03 dL / g.

[0102] Example 4

[0103] Preparation of modified heterocyclic aramid copolymer

[0104] The specific synthesis steps are as follows:

[0105] Step 1 Synthesis of modified heterocyclic aramid crude product

[0106] In a reactor equipped with a nitrogen device and a thermometer, purify the nitrogen and aerate for 20 minutes in advance, then add 20 parts by mass of dehydrated anhydrous LiCl and 1000 parts by mass of DMF, and mix and dissolve at room temperature. Add 5.4 parts by mass of PPD, 10.3 parts by mass of APBIA, and 10.8 parts by mass of 4-(4-amino-3,5-dimethylbenzyl)-2,6-dimethylaniline in batches. During this process, to prevent oxidation and lower the solution temperature, place the system in a cooling circulation bath and cool it to -10 to -5°C. Continue stirring and add 26.39 parts by mass of TPC in batches. Use 18.86 parts by mass of pyridine to neutralize the by-product HCl generated in the polymerization reaction. React for 90 minutes to obtain a gel-like product;

[0107] Step 2 Modified heterocyclic aramid product

[0108] After pulverizing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain a light yellow pulp ultra-short fiber modified heterocyclic aramid copolymer, named PPAIN 45-2 . The monomer conversion rate is 96.20%. The average fiber length is greater than 4.9 mm; η inhIt is 5.35 dL / g.

[0109] Example 5

[0110] Preparation of modified heterocyclic aramid copolymer

[0111] The specific synthesis steps are as follows:

[0112] The first step: Synthesis of crude modified heterocyclic aramid

[0113] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, and mix and dissolve at room temperature. Add 21.6 parts by mass of PPD, 22.8 parts by mass of APBIA, and 21.6 parts by mass of DDS in batches. During this process, to prevent oxidation and to lower the solution temperature, place the system in a cooling circulation bath and cool it to -10 to -5 °C. Continue stirring and add 105.6 parts by mass of TPC in batches. Use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction, and react for 50 minutes to obtain a gel-like product;

[0114] The second step: Fine modified heterocyclic aramid

[0115] After crushing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain light yellow pulp ultra-short fiber modified heterocyclic aramid, named PPAIS 25 . The monomer conversion rate is 71.91%. The average fiber length is greater than 5.3 mm; η inh is 3.17 dL / g.

[0116] Example 6

[0117] Preparation of modified heterocyclic aramid copolymer

[0118] The specific synthesis steps are as follows:

[0119] The first step: Synthesis of crude modified heterocyclic aramid

[0120] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 30 parts by mass of 3 wt% dehydrated anhydrous CaCl₂ and 1000 parts by mass of DMSO, and mix and dissolve at room temperature. Add 21.6 parts by mass of PPD, 13.68 parts by mass of APBIA, and 30.2 parts by mass of 3,3'-5,5'-methylbiphenyldiamine in batches. During this process, to prevent oxidation and lower the solution temperature, place the system in a cooling circulation bath and cool it to -10 to -5 °C. Continue stirring and add 105.6 parts by mass of TPC in batches. Use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction, and react for 150 minutes to obtain a gel-like product;

[0121] Step 2 Modified heterocyclic aramid fine product

[0122] After crushing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain a light yellow pulp ultra-short fiber modified heterocyclic aramid copolymer, named PPAIN 15 The monomer conversion rate is 95.01%. The average fiber length is greater than 5.4 mm; η inh is 3.85 dL / g.

[0123] Example 7

[0124] Preparation of modified heterocyclic aramid copolymer

[0125] The specific synthesis steps are as follows:

[0126] Step 1 Synthesis of modified heterocyclic aramid crude product

[0127] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 5 parts by mass of dehydrated anhydrous LiCl and 500 parts by mass of DMAC, and mix and dissolve at room temperature. Add 21.6 parts by mass of PPD, 13.68 parts by mass of APBIA, and 30.2 parts by mass of 3,3'-diaminodiphenyl sulfone in batches. During this process, to prevent oxidation and lower the solution temperature, place the system in a cooling circulation bath and cool it to -20 °C. Continue stirring and add 105.6 parts by mass of TPC in batches. Use 18.8 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction, and react for 240 minutes to obtain a gel-like product;

[0128] Step 2 Modified heterocyclic aramid fine product

[0129] After crushing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain a light yellow pulp ultra-short fiber modified heterocyclic aramid copolymer, named PPAIS 15-1 The monomer conversion rate is 88.48%. The average fiber length is greater than 5.3 mm; η inhIt is 3.40 dL / g.

[0130] Example 8

[0131] Preparation of Modified Heterocyclic Aromatic Polyamide Copolymer

[0132] The specific synthesis steps are as follows:

[0133] The First Step: Synthesis of Crude Modified Heterocyclic Aromatic Polyamide

[0134] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 10 parts by mass of dehydrated anhydrous LiCl and 2000 parts by mass of DMF, dissolve CaCl2 at room temperature, add 21.6 parts by mass of PPD, 36.5 parts by mass of APBIA, and 8.64 parts by mass of DDS in batches. During this process, to prevent oxidation and lower the solution temperature, place the system in a cooling circulation bath and cool it to 0 °C; continue stirring and add 97.4 parts by mass of TPC in batches; use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction, and react for 120 minutes to obtain a gel-like product;

[0135] The Second Step: Fine Modified Heterocyclic Aromatic Polyamide

[0136] After crushing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain a light yellow pulp ultra-short fiber modified heterocyclic aromatic polyamide copolymer, named PPAIS 40 . The monomer conversion rate is 89.16%. The average fiber length is greater than 4.9 mm; η inh is 4.40 dL / g.

[0137] Appendix Figure 2 The diamine composition of the modified heterocyclic aromatic polyamide quaternary copolymer (PPAIS of Example 1 45 , PPAIS of Example 8 40 and PPAIS of Example 3 35 ) is p-phenylenediamine: 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA): diaminodiphenylsulfone with a molar ratio of 50:45:5, 50:40:10, 50:35:15 respectively. As the amount of diaminodiphenylsulfone increases, the peaks of para-aramid at 2θ of 21.1°, 23.4° and 28.5° become obvious again, indicating enhanced local crystallization order. New sharp peaks appear at 2θ of 17.1° and 25.0°, indicating that the polymer order disrupted by APBIA is reconstructed by DDS.

[0138] Appendix Figure 3 The modified heterocyclic aromatic polyamide PPAIS of Example 1 45 quaternary copolymer, PPAIS of Example 8 40and the PPAIS of Example 3 35 The weight loss of several samples was slow, and the PPAIS 45 had a residual carbon content of over 50% at 800 °C and good thermal stability. From Figure 3 comparison, it can be seen that the heat resistance of the modified heterocyclic aramid PPAIS 45 tetracopolymer was the best.

[0139] Example 9

[0140] Preparation of modified heterocyclic aramid copolymer

[0141] The specific synthesis steps are as follows:

[0142] The first step: Synthesis of crude modified heterocyclic aramid

[0143] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, dissolve CaCl2 at room temperature, add 21.6 parts by mass of PPD, 27.4 parts by mass of APBIA, and 17.28 parts by mass of DDS in batches. During this process, to prevent oxidation and to lower the solution temperature, the system needs to be placed in a cooling circulation bath and cooled to -5 °C, continue stirring, add 97.4 parts by mass of TPC in batches, and use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction. React for 120 - 150 minutes to obtain a gel-like product;

[0144] The second step: Fine modified heterocyclic aramid

[0145] After crushing and thoroughly washing it, dry it to a constant weight in a vacuum drying oven to obtain a light yellow pulp ultra-short fiber modified heterocyclic aramid copolymer, named PPAIS 30 . The monomer conversion rate was 88.21%. The average fiber length was greater than 4.8 mm; η inh was 4.76 dL / g.

[0146] Comparative Example 1

[0147] Preparation of binary para-aramid PPTA

[0148] The specific synthesis steps are as follows:

[0149] The first step: Synthesis of crude para-aramid

[0150] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes in advance, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, dissolve CaCl2 by mixing at room temperature, add 21.6 parts by mass of PPD in batches. During this process, to prevent oxidation and to lower the solution temperature, the system needs to be placed in a cooling circulation bath and cooled to -5 °C. Continue stirring and add 52.8 parts by mass of TPC in batches. Use 97.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction. React for 120 - 150 minutes to obtain a poorly soluble gel-like product;

[0151] Step 2 Para-aramid fine product

[0152] After pulverizing and thoroughly washing it, dry it to constant weight in a vacuum drying oven to obtain dark yellow powder. The monomer conversion rate is 85.42%. η inh is 5.29 dL / g.

[0153] In Comparative Example 1, the para-aramid PPTA has a regular structure. In the synthesized salt solvent, solid powder precipitates, making it difficult to directly spin with organic solvents, that is, the solubility of PPTA in the polymerization reaction solvent is poor. After dissolving PPTA in concentrated sulfuric acid for spinning, due to orientation and strong hydrogen bonds, the internal cohesive property of the fiber side is weak, the compressive strength between the fiber cortex and the middle matrix is low, and the interfacial interaction is poor. There is a skin-core effect in PPTA fibers.

[0154] Appendix Figure 1 In, the curve of PPTA in Comparative Example 1 is poly(p-phenyleneterephthalamide) (PPTA). It can be observed from the figure that in the range of 3420 - 3220 cm- 1 the absorption band observed is attributed to the stretching vibration of -NH in PPTA. The three typical absorption bands unique to the amide group are 3320 cm -1 , 1513 cm -1 , 1240 cm -1 , coming from the stretching vibration of N-H, the deformation vibration of N-H, and the stretching vibration of C-N respectively. The peak at 1643 cm -1 corresponds to the stretching vibration of C=O.

[0155] From the PPTA curve of Comparative Example 1 in Appendix Figure 2 it can be observed that the para-aramid binary copolymer of PPTA shows three relatively sharp and obvious peak positions at 2θ of 21.1° (110 crystal plane), 23.4° (200 crystal plane), and 28.5° (004 crystal plane) respectively, which are the crystallization characteristic peaks of para-aramid.

[0156] From Appendix Figure 2 the curve of the modified heterocyclic aramid PPAIS quaternary copolymer (PPAIS in Example 1)45 and the PPAIS of Example 8 40 and the PPAIS of Example 3 35 ) It can be seen that compared with the PPTA of Comparative Example 1, there are obvious crystallization signal peaks in each curve of the modified heterocyclic aramid PPAIS quaternary copolymer.

[0157] Appendix Figure 3 Thermogravimetric curve of the binary copolymer PPTA of Comparative Example 1.

[0158] Comparative Example 2

[0159] Preparation of terpolymer aramid

[0160] The specific synthesis steps are as follows:

[0161] The first step: Synthesis of crude terpolymer aramid

[0162] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, dissolve CaCl2 at room temperature, and add 21.6 parts by mass of PPD and 45.6 parts by mass of APBIA in batches. During this process, to prevent oxidation and lower the solution temperature, the system needs to be placed in a cooling circulation bath and cooled to -5°C. Continue stirring and add 97.44 parts by mass of TPC in batches. Use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction, and react for 120 - 150 minutes to obtain a gel-like product;

[0163] The second step: High-quality terpolymer aramid

[0164] After crushing and thoroughly washing it, dry it to constant weight in a vacuum drying oven to obtain a golden-brown powder, named PPAI 50 . The monomer conversion rate is 91.01%. η inh is 5.10 dL / g.

[0165] Aramid III usually refers to the polymer formed by polymerizing PPD, APBIA, and TPC, which is abbreviated as PPAI in this article.

[0166] Appendix Figure 1 In Appendix, the aramid PPAI curve of Comparative Example 2 shows that the peak at 1592 cm -1 in the terpolymer of aramid PPAI corresponds to the vibration of the C-N in the imidazole ring of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA).

[0167] Appendix Figure 2In the case of meta-aramid III, i.e., the PPAI curve of Comparative Example 2 showed a relatively large peak at 22.5°. There were small crystallization peaks at 2θ of 21.1° and 23.4°, and the peak positions were the same as those of PPTA (from 2θ of 15.8 to 33.0°), indicating the coexistence of local crystalline regions and amorphous regions in the micro-aramid. It shows that the polymer order disrupted by APBIA is beneficial to enhancing the toughness of aramid.

[0168] Attachment Figure 3 Aramid terpolymer PPAI of Comparative Example 2 50 Thermogravimetric curve.

[0169] Table 1 is attached Figure 3 Data comparison of thermogravimetric tests shows that the residual polymer content of the modified heterocyclic aramid PPAIS 45 quaternary copolymer (Example 1) exceeds that of para-aramid PPTA (Comparative Example 1). PPAIS 45 and PPAIS 40 (Example 8) has a residual polymer content exceeding that of aramid PPAI 50 (Comparative Example 2). PPAIS 45 The initial temperature of 5% weight loss is much higher than that of PPTA and PPAI 50 . Figure 3 And Table 1 shows that the modified heterocyclic aramid quaternary copolymer has excellent heat resistance.

[0170] Table 1 Thermogravimetric relationship of PPTA, PPAI 50 and PPAIS with temperature

[0171]

[0172] Comparative Example 3

[0173] Preparation of terpolymer aramid

[0174] The specific synthesis steps are as follows:

[0175] First step Synthesis of terpolymer aramid crude product

[0176] In a reactor equipped with a nitrogen device and a thermometer, first purge with pure nitrogen for 20 minutes, then add 30 parts by mass of dehydrated anhydrous CaCl2 and 1000 parts by mass of NMP, dissolve CaCl2 at room temperature, add 21.6 parts by mass of PPD and 19.57 parts by mass of APBIA in batches. During this process, to prevent oxidation and to lower the solution temperature, the system needs to be placed in a cooling circulation bath and cooled to -5°C, continue stirring, add 69.6 parts by mass of TPC in batches, and use 75.4 parts by mass of 2-methylpyridine to neutralize the by-product HCl generated in the polymerization reaction. React for 120 - 150 minutes to obtain a poorly soluble gel-like product;

[0177] Step 2 Ternary Copolymerized Aramid Fine Product

[0178] After pulverizing and thoroughly washing it, it was dried in a vacuum drying oven at 150 °C for 8 hours until constant weight, obtaining a golden-brown powder, named PPAI 30 . The monomer conversion rate was 92.43%. η inh was 3.54 dL / g.

[0179] PPAI 30 refers to the molar ratio of PPD:APBIA = 70:30

[0180] Table 2 Solubility Comparison of Modified Heterocyclic Aramid PPAIS Quaternary Copolymer, Ternary Copolymerized Aramid PPAI and Para-Aramid PPTA

[0181]

[0182] Note: × Insoluble; √ Soluble; ▲ Slight swelling; PPAIS Quaternary Copolymerized Aramid; PPAI Ternary Copolymerized Aramid; PPTA Para-Aramid

[0183] PPAIS 45 refers to the molar ratio of PPD:APBIA:DDS = 50:45:5.

[0184] In Comparative Example 1 of Table 2, para-aramid PPTA was insoluble in all solvents except concentrated sulfuric acid, indicating that it is only suitable for spinning and forming with concentrated sulfuric acid.

[0185] In Comparative Example 3 of Table 2, ternary copolymerized aramid PPAI 30 was insoluble in all solvents except concentrated sulfuric acid, indicating that it is only suitable for spinning and forming with concentrated sulfuric acid. When the content of 2-(4-aminophenyl)-5-aminobenzimidazole APBIA was low, the properties of ternary aramid were the same as those of PPTA.

[0186] In Comparative Example 2 of Table 2, ternary copolymerized aramid PPAI 50 had similar solubility to quaternary copolymerized aramid.

[0187] Table 2 shows the solubility of samples of each example and comparative example of the present invention. The modified heterocyclic aramid quaternary copolymer is expected to achieve spinning with organic solvents.

[0188] The improved solubility of the modified heterocyclic aramid quaternary copolymer enables it to abandon the harsh concentrated sulfuric acid spinning of aramid fibers and only requires adding a small amount of inorganic salt ions to a polar solvent for effective spinning; this reduces the cost and, more importantly, reduces the danger level during the spinning process and subsequent processing, which is in line with the concept of green chemistry. The fibers prepared from the modified heterocyclic aramid not only improve the problems of difficult dissolution of PPTA and easy brittle fracture of the spun samples but also solve the problem of low axial compressive strength. The small amount of flexible self-entangling structure and the mostly rigid and ordered molecular chains of the modified heterocyclic aramid not only improve its solubility during the spinning process but also endow the fibers prepared from it with excellent impact resistance due to their unique entangled structure characteristics.

[0189] Application Example 1

[0190] Modified heterocyclic aramid PPAIS 45 Preparation of the quaternary copolymer and polyurethane foam composite material

[0191] The modified heterocyclic aramid PPAIS prepared in Example 1 45 The copolymer was applied to the field of composite materials. The specific coating process is as follows: The modified heterocyclic aramid PPAIS 45 polymer was dissolved in a DMF solvent containing 5% KOH to prepare an aramid nanofiber dispersion; the polyurethane foam was immersed in the modified heterocyclic aramid dispersion for 36 h; after passing through a coagulation bath, solvent replacement, and freeze-drying, an aramid-polyurethane foam composite material was obtained, named PPAIS-RPUF; the coagulation bath was a mixed solution of acetic acid and water, the mass concentration of acetic acid was 5%, and the temperature of the modified heterocyclic aramid solution (aerogel) was 25°C.

[0192] The microscopic morphology of the modified heterocyclic aramid quaternary copolymer (aerogel) prepared in Application Example 1 is as Figure 6 shown. From Figure 6 it can be seen that the aramid (aerogel)-polyurethane foam composite material obtained using the modified heterocyclic aramid PPAIS polymer has dense and uniform pores, and the holes are evenly filled. This method is conducive to the full coverage penetration of aramid, improves the fire resistance and high-temperature resistance of polyurethane foam, and broadens its scope of use.

[0193] Figure 6 This is the optical microscope image of Application Example 1 of the present invention, which shows the use of the PPAIS 45 copolymer in Example 1.

[0194] Appendix Figure 6 is the optical microscope photograph of the composite material of the modified heterocyclic aramid quaternary copolymer PPAIS 45 aerogel and polyurethane foam, indicating a good composite situation; PPAIS 45Filling the internal pores of the polyurethane foam to achieve good compatibility of the semi-interpenetrating network and intermolecular hydrogen bonds.

[0195] By directly igniting the PPAIS-RPUF composite material and the polyurethane foam with an alcohol lamp respectively, the combustion experiment proves that the modified heterocyclic aramid PPAIS prepared in Example 1 45 The polymer endows the polyurethane foam with thermal stability and biological protection; and through the combustion experiment in the air, it is proved that PPAIS-RPUF has flame-retardant self-extinguishing heat insulation performance, providing more application possibilities for this material.

[0196] In Table 3, the limiting oxygen index LOI of the PPAIS-RPUF composite material burning in the nitrogen-oxygen mixed gas is 25.8, which is 16.7% higher than that of the polyurethane foam RPUF sample (22.1). The char residue rate of PPAIS-RPUF after combustion in the muffle furnace is 24.4% higher than that of RPUF.

[0197] Table 3 LOI and char residue rate of RPUF and PPAIS-RPUF after nitrogen-oxygen mixed gas.

[0198]

[0199] Remarks: a is the result of combustion in the nitrogen-oxygen mixed gas. b is the result of combustion in the air.

[0200] Table 4 Thermogravimetric data shows that the weight loss of the modified heterocyclic aramid aerogel-polyurethane foam composite material at 420 °C is 13.61% less than that of the blank polyurethane foam.

[0201] Table 4 Weight loss situation and main heat loss temperature of the thermogravimetric curves of RPUF and PPAIS-RPUF

[0202]

[0203] In addition, it should be noted that when the solvent N-methylpyrrolidone in the embodiments of the present invention is replaced with N,N-dimethylacetamide, etc.; and the co-solvent calcium chloride is replaced with lithium chloride, etc., the well-soluble modified heterocyclic aramid quaternary copolymer of the present invention can be obtained.

[0204] In the reaction of the present invention, the reaction time is short and the conversion rate is high. A modified heterocyclic aramid copolymer with good compatibility and high solubility is prepared by a low-temperature solution polycondensation process. The synthesis route and process are simple, the raw materials are widely available, inexpensive and easy to obtain, and the process is stable. The present invention also provides new uses for modified aramid. The aramid aerogel has good compatibility with polyurethane, is flame-retardant, self-extinguishing, heat-insulating, bioprotective, high-temperature resistant, insulating, and is used in electric vehicles, etc. to solve the problem of spontaneous combustion of electric vehicles and protect the lives of passengers. It can be formed or spun using a specific solvent other than sulfuric acid, which has certain theoretical significance and industrial value for the improvement of aramid spinning.

[0205] Uses:

[0206] The long fibers of the modified heterocyclic aramid copolymer can be used to prepare aramid cloth, and the modified heterocyclic aramid pulp and short fibers can be used to prepare aramid paper, aramid honeycomb, etc. The modified heterocyclic aramid and its composites of the present invention can be used in bend-resistant optical fibers, communication materials, aerospace, and electric vehicles, etc. to solve the problem of spontaneous combustion of electric vehicles.

[0207] It can be applied to multiple parts of automobiles such as brake pads, clutches, hoses, tires, shock absorbers, etc., and is used for components in the braking, power, transmission, and driving systems of automobiles, and has super wear resistance, high temperature resistance, high strength, fire resistance, etc. that ordinary accessories cannot match.

[0208] The flame-retardant aramid fiber can withstand high temperatures of 200 °C for a long time, is difficult to ignite in the air, does not self-ignite, is non-toxic and odorless, and has good dimensional stability. It is an ideal safety material for automobile interiors (automobile seats, seat belts). The speaker made of aramid woven fabric reduces distortion, prevents breakage of sound, improves the off-axis diffusion performance of the sound, and improves the sound field effect.

[0209] The brake pads processed from aramid pulp with high temperature resistance and wear resistance reduce braking noise, shorten the braking distance, extend the service life, and reduce the replacement frequency. The aramid with heat and chemical resistance, firmness and lightness can be used to reinforce automotive hoses such as radiators, gearboxes, and turbocharger hoses. Composites such as aramid are used as the skeleton reinforcing material for clutch gaskets, which can ensure the stability of the high-temperature friction of the clutch. The high-strength, wear-resistant, and heat-dissipating aramid cord is used for the carcass, crown ply, belt layer, etc. of automobile and truck tires, which can reduce resistance, reduce energy consumption, enhance grip, reduce vibrations caused by impacts and jumps, and have fast braking and smooth driving.

[0210] The high-strength and high-modulus aramid cord is used for synchronous belts, which is wear-resistant, has extremely high tensile properties and breaking strength, and greatly extends the service life. Aramid pulp and chopped fibers are used for non-metallic gears, which have characteristics such as high temperature resistance, high strength, wear resistance, and good dimensional stability, good dispersibility, are suitable for reinforcing engineering plastics, and the processed automobile non-metallic gears have functions such as being strong and durable, light in weight, electrically insulating, low in noise, and corrosion-resistant.

[0211] The protection scope of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be conceived by those skilled in the art are included in the present invention, and the appended claims are used as the protection scope.

Claims

1. A modified heterocyclic aramid, the structural formula of which is as follows: ; In the formula, m is 20 - 400; n is 20 - 400; r is 4 - 210; Ar, the diamino fourth monomer, is the residue other than the amino group in the following compounds: 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 3,3'-diaminodiphenyl sulfone, 1,5-naphthalenediamine, 2,6-naphthalenediamine, 1,6-naphthalenediamine, 1,7-naphthalenediamine, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, 4-(4-amino-3,5-dimethylbenzyl)-2,6-dimethylaniline or 3,3',5,5'-tetramethylbenzidine.

2. A method for preparing the modified heterocyclic aramid according to claim 1, characterized in that: Synthesized by the one-pot method, specifically including: Step 1: Synthesis of the crude modified heterocyclic aramid In a reactor equipped with a nitrogen device and a thermometer, pure nitrogen is introduced, and then the dehydrated cosolvent and solvent are added and mixed and dissolved; p-phenylenediamine (PPD), 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and the fourth monomer are added, and the temperature is lowered to -20 - 0 °C; continue stirring, and p-phthaloyl chloride (TPC) is added in batches; an acid-binding agent is used to neutralize the by-product HCl generated by the polymerization reaction; the reaction time is extended to obtain a gel-like product, i.e., the crude product; Step 2: Refinement of the modified heterocyclic aramid The crude product obtained in Step 1 is precipitated, pulverized, washed thoroughly, and then dried to a constant weight in a vacuum drying oven to obtain a light yellow modified aramid pulp, i.e., the ultra-short fiber copolymer, which is the modified heterocyclic aramid; the specific synthesis route is as shown in Formula (1): ; (1) In Step 1, the solvent is one or more of N-methylpyrrolidone (NMP), N,N'-dimethylacetamide, N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); The cosolvent is lithium chloride or calcium chloride; The content of the cosolvent is 0.5 - 5 wt% of the total solution; In Step 1, the reaction temperature is -20 - 5 °C; In Step 1, the reaction time is 90 - 240 minutes; In Step 1, the acid-binding agent is α-methylpyridine or pyridine; The mass ratio of p-phthaloyl chloride (TPC) : p-phenylenediamine (PPD) : 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) : the fourth monomer : the solvent : the cosolvent : the acid-binding agent is 1 : 0.20 - 0.30 : 0.13 - 0.46 : 0.04 - 0.41 : 9.47 - 37.90 : 0.047 - 0.76 : 0.17 - 0.

84.

3. Use of the modified heterocyclic aramid according to claim 1 in the preparation of aramid-polyurethane foam composites.

Citation Information

Patent Citations

  • High-performance heterocyclic aramid fiber as well as preparation and application thereof

    CN101921395A

  • White high-thermal-conductivity para-aramid fiber and preparation method thereof

    CN118854479A

  • Para-aramid staple fiber, aramid spun yarn and manufacturing method threof

    US20240368808A1